Land suitability evaluation for surface irrigation development using parametric evaluation approach: The case of Gudina Wacho watershed, Western Ethiopia - Gebre Gidey Weldeabzgi; Tekalign Ketema; Gezahegn Gashu; Sime Deressa (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Evaluating land suitability of a given watershed is vital to predict potential and limitation of the land for surface irrigation. The present study was evaluated the suitability of Gudina Wacho watershed for surface irrigation development using parametric evaluation approach. The watershed was classified in to four lands mapping units, based on three soil profile pits were opened at each land mapping unit. Soil samples from each profile pit have been taken to analyze each selected soil physical and chemical properties. Slop analysis of the watershed was computed from the DEM using GIS technique. Results of the land suitability evaluation for surface irrigation showed that, a total area of 3064 ha (72.6%) was slightly suitable (S3) and area of 1154 ha (27.4%) was currently not suitable (N1). The limiting factors were slop, soil texture and drainage. For all land mapping units, chemical soil parameters such as CaCO3, ECe and pH, and the physical parameter (soil depth) were not limiting factors for surface irrigation in the study watershed. Therefore, the area is potential for irrigation production with some limitations and under proper management it can benefit the local community to meet the food demand. In order to sustainably develop the area for irrigation development; land leveling operation or soil conservation work has to be incorporated to break surface slope and to make it suitable for surface irrigation.